The importance of websites to the issue of people with disabilities - حمەکریم, م.ی. رەفیق صابر; سعید, م.ی. کوێستان قادر; امین, م.ی. شنە احمد (Sulaimani Journal for Humanities, 2025)
This study is an attempt to be aware of the importance of Kurdish news websites by paying attention and publishing the issue of people with disabilities, who are an important and sensitive section of society. It is followed by a descriptive method and using content analysis methodology, through the analysis form tool. (46) media articles published randomly on the website (K24), within six months from (1/7/2023 to 31/12/2023) were identified as research samples and analyzed. The aim of the research is to: - To determine the extent of presentation of the problems of people with disabilities in Kurdish websites, as well as the level of attention of websites to the issue of people with disabilities and the extent of consideration of their situation. The most important conclusions reached by the study are: 1. K24 website has paid a lot of attention to the problems related to the livelihood of people with disabilities, with the social relationships they face in society, and have not been able to provide them with opportunities to find their own jobs. 2. K24 has tried to take into account all the issues related to people with disabilities, first of all paying attention to health issues, then considered economic issues. 3. K24 website has paid the most attention to written and video formats and the least attention to sign language, while some people with disabilities such as blind and deaf cannot receive media messages. He also tried to use the phrases used to express the problems and issues of people with disabilities in a positive way and described them in a strong way.
Keywords: Value; website; disabled